AB0977 Prevalence of Subclinical Synovitis Detected by Ultrasound in Rheumatoid Arthritis and Psoriatic Arthritis Patients Receiving Anti-TNF Therapy with Extended Interval of Administration. (10th June 2014) - Senabre Gallego, J.M.; Rosas, J.; Salas Heredia, E.; Santos Soler, G.; Llinares Tello, F.; Santos Ramírez, C.; Sánchez Barrioluengo, M.; Barber, X.; Ortega, R.; Pons, A.; Cano, C.; Lorente, M.I.
Abstract : Objectives: To estimate the prevalence of subclinical synovitis detected by ultrasound in rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients in clinical remission receiving anti-TNFα therapy with extended interval of administration (EIA). Methods: Prospective observational study. Population: Patients diagnosed with RA and PsA, receiving anti-TNFα and being in clinical remission. 12-joint ultrasound assessment (elbows, wrists, 2nd and 3rd metacarpo-phalangeal, knees and ankles) 1 was performed, evaluating synovitis through B-mode (BM) and Color Doppler signal (CD), both by semiquantitative scale from 0 to 3 points (Esaote MyLab 25). Subsequently, a BM and CD score was calculated, summing the highest score obtained from any one of the synovial sites evaluated at each joint to a maximum of 36 points. The sonographer was blinded to the clinical and laboratory data. Results: 34 patients were included in the study, 70.6% were women, mean age was 60 years [32-81] and mean duration of disease was 14.6 years [3-46]. The diagnosis was RA in 30 patients (88.2%) and APs in 4 (11.7%). In 86.7% of patients with RA rheumatoid factor was positive, and in 76.7% the citrullinated protein antibody was positive. Ultrasound assessment prior to EIA was available in 24 patients, and after EIA in 23 patients. Clinical activity and ultrasound scores are summarized in Table 1 . Ultrasound detects some synovitis by CD in 52% of EIA patients, and by BM in 78% of EIA patients. Nevertheless most of them had a low CD score (average 1.3 out of 36 points). The EIA treatments were etanercept (ETN) in 13 patients and adalimumab (ADA) in 10 patients, with the following patterns: ETN/10 days (11 pat.), ETN/14 days (1 pat.), ETN/15 days (1 pat.), ADA/18 days (6 pat.), ADA/21 days (2 pat.), ADA/17 days (1 pat.), ADA/30 days (1 pat.). Six patients (24%) never began EIA due to clinical decision, and 7 (29%) had to return to the standard administration pattern due to worsening of disease activity. Conclusions: Some synovitis was detected by Color Doppler ultrasound in 52% of patients in clinical remission receiving anti-TNFα therapy with extended interval of administration. Most of them had a low Color Doppler ultrasound score. Synovial hypertrophy was detected by B-mode ultrasound in 78% of them. References: Naredo E. Arthritis Rheum 2008, 59:515-22. Acknowledgements: This work was supported by a grant from Fundaciόn Española de Reumatología. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2990